2015
DOI: 10.1089/chi.2014.0124
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Child/Adolescent Obesity Using the Addiction Model: A Smartphone App Pilot Study

Abstract: Background: The aim of this study was to test a weight loss program for young people based on an addiction treatment approach.Methods: A pilot study (n=43) was conducted of a 20-week child/adolescent obesity intervention based on an addiction treatment model (staged, incremental withdrawal from problem foods, snacking/grazing, and excessive amounts at meals) and implemented by a server-integrated smartphone app with health professional support. The primary outcome was standardized %overBMI measured at four tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
115
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(117 citation statements)
references
References 23 publications
(19 reference statements)
2
115
0
Order By: Relevance
“…Adherence to preventive behavior was evaluated by clinic attendance in 4 [35,36,39,53], self-report of adherence in 3 [37,40,50], self-report and electronic device to monitor adherence in 1 [38], and electronic direct observation of adherence behavior (self-photographs or selfies) in 1 study [46]. All the included studies provided enough information to calculate standardized outcomes (ie, effect sizes d or SMDs), except 1 [42].…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to preventive behavior was evaluated by clinic attendance in 4 [35,36,39,53], self-report of adherence in 3 [37,40,50], self-report and electronic device to monitor adherence in 1 [38], and electronic direct observation of adherence behavior (self-photographs or selfies) in 1 study [46]. All the included studies provided enough information to calculate standardized outcomes (ie, effect sizes d or SMDs), except 1 [42].…”
Section: Resultsmentioning
confidence: 99%
“…Study, program and participant characteristics are reported in Table . Half of the programs were from the United States (US; n = 11) with the remainder from Europe ( n = 7) , Australia ( n = 2) and the United Kingdom (UK; n = 1) . The programs were evaluated as controlled trials ( n = 15), both randomized ( n = 10) and non‐randomized ( n = 5) , and as pre–post case series ( n = 6) .…”
Section: Resultsmentioning
confidence: 99%
“…Study quality was assessed to be weak for five programs ; moderate for eight ; and strong for eight . More than half of the programs were rated as being weak for selection bias ( n = 11) , as they involved self‐referrals from community advertisements and public service announcements, as is commonplace for community interventions, and thus participants were not selected at random from the eligible population.…”
Section: Resultsmentioning
confidence: 99%
“…According to Schwarz et al [39] given the current support for some sort of a mediating or moderating relationship to obesity in selected cases, a psychodynamically oriented approach to treating compulsive overeating, as well as an integrated model, rather than a medical model of intervention alone may be helpful for reducing obesity in selected cases. In addition, given the similarities of food addiction to other addictive behaviors Dimitrijovic et al [1] have advocated for the application of traditional addictive treatment approaches in the context of treating obesity, while a staged or incremental food withdrawal approach may be helpful as outlined by Pretlow et al [31].…”
Section: Resultsmentioning
confidence: 99%